SCHEDULED FOG IRIGATION SYSTEM USING ARDUINO UNO AND RTC (REAL-TIME CLOCK) ON FERTILIZATION OF MUSTARD PLANT (Brassica juncea L.) - De Side, Gagassage Nanaluih; Sumarsono, Joko; Abdullah, Sirajuddin Haji; Priyati, Asih; Dewi, Endang Purnama; Wenny Amaliah (Jurnal Teknologi Pertanian, 2024)
The watering of seedings can be done automatically by leveraging the development and advancement of technology, one of which is by utilizing a microcontroller that can be programmed to do watering according to the preferred time. This research aims to design and implement a scheduled fog irrigation system using the Arduino UNO microcontroller and utilizing the RTC (real-time clock) component in the mustard green seeding. In this research, the fog irrigation system is applied to green cabbage by optimizing the Arduino Uno microcontroller, which is used to design electronic circuits to automate the control of watering fog irrigation. Through this system, it is expected that plant watering can be done on time and the plant's water needs can be fulfilled. This research uses the experimental method or experiments with direct observation in the field through several stages, including preparing, designing, and making irrigation installations, constructing a series of scheduled fog irrigation systems, making scheduled irrigation program languages, calibrating RTCs, and working on scheduled fog irrigation systems. The research parameters include water use efficiency and the operation of the scheduled fog irrigation system. The observation parameters were water discharge (mL/min), water use efficiency (%), plant height (cm), number of leaves (strands), and performance of the scheduled fog irrigation system. Three treatments were applied in this study: first-time watering, second times watering, and third times watering. The scheduled fog irrigation system ran well during the research and aligned with the plan. In testing, the fog irrigation system has a water use efficiency of 75.86%, and in the treatment of fog irrigation, three times a day has the highest value of height and number of leaves with an average height of 3.72 cm and an average number of leaves 2.77 strands.